Model Pengembangan Kewirausahaan Berbasis Gerakan Kemandirian Ekonomi di Lingkungan Muhammadiyah Limbung Gowa - Siti Walida Mustamin; Hasanuddin, Hasanuddin; Reski Adi (Al-Buhuts, 2023)
This article aims to analyze and develop an entrepreneurship development model based on the economic independence movement in the Muhammadiyah Limbung Gowa environment. The research method used is qualitative with a case study approach. Data was collected through in-depth interviews, observation and documentation studies. The informants consisted of Muhammadiyah figures, branch administrators and unsteady Muhammadiyah leaders. The research results show that the Muhammadiyah Limbung Gowa environment has great potential in developing entrepreneurship. However, there are still challenges such as a lack of understanding of the concept of entrepreneurship and a lack of access to capital and entrepreneurship training. Based on these findings, this research proposes an entrepreneurship development model that involves a collaborative approach between Muhammadiyah, the government and the private sector in providing assistance, training and access to capital for aspiring entrepreneurs. Apart from that, this model also encourages strengthening networks between entrepreneurs to support local economic growth